Antiproliferative and apoptosis-inducing activity of an oxidovanadium(IV) complex with the flavonoid silibinin against osteosarcoma cells - León, Ignacio Esteban (2014)
Flavonoids are a large family of polyphenolic compounds synthesized by plants. They display interesting biological effects mainly related to their antioxidant properties. On the other hand, vanadium compounds also exhibit different biological and pharmacological effects in cell culture and in animal models. Since coordination of ligands to metals can improve or change the pharmacological properties, we report herein, for the first time, a detailed study of the mechanisms of action of an oxidovanadium(IV) complex with the flavonoid silibinin, Na₂[VO(silibinin)₂]·6H₂O (VOsil), in a model of the human osteosarcoma derived cell line MG-63. The complex inhibited the viability of osteosarcoma cells in a dose-dependent manner with a greater potency than that of silibinin and oxidovanadium(IV) (p < 0.01), demonstrating the benefit of complexation. Cytotoxicity and genotoxicity studies also showed a concentration effect for VOsil. The increase in the levels of reactive oxygen species and the decrease of the ratio of the amount of reduced glutathione to the amount of oxidized glutathione were involved in the deleterious effects of the complex. Besides, the complex caused cell cycle arrest and activated caspase 3, triggering apoptosis as determined by flow cytometry. As a whole, these results show the main mechanisms of the deleterious effects of VOsil in the osteosarcoma cell line, demonstrating that this complex is a promising compound for cancer treatments.